Microtubular Fuel Cell with Ultrahigh Power Output per Footprint. Issue 34 (10th July 2017) - Miao, Shiding; He, Shulian; Liang, Mengnan; Lin, Gungun; Cai, Bin; Schmidt, Oliver G.
Abstract : A novel realization of microtubular direct methanol fuel cells ( µ DMFC) with ultrahigh power output is reported by using "rolled‐up" nanotechnology. The microtube (Pt‐RuO2 ‐RUMT) is prepared by rolling up Ru2 O layers coated with magnetron‐sputtered Pt nanoparticles (cat‐NPs). The µ DMFC is fabricated by embedding the tube in a fluidic cell. The footprint of per tube is as small as 1.5 × 10 −4 cm 2 . A power density of ≈257 mW cm −2 is obtained, which is three orders of magnitude higher than the present microsized DFMCs. Atomic layer deposition technique is applied to alleviate the methanol crossover as well as improve stability of the tube, sustaining electrolyte flow for days. A laminar flow driven mechanism is proposed, and the kinetics of the fuel oxidation depends on a linear‐diffusion‐controlled process. The electrocatalytic performance on anode and cathode is studied by scanning both sides of the tube wall as an ex situ working electrode, respectively. This prototype µ DFMC is extremely interesting for integration with micro‐ and nanoelectronics systems. Abstract : A novel realization of microdirect methanol fuel cells (µDMFC) is presented by utilizing rolled‐up nanotechnology. A power density of 257 mW cm −2 is obtained, which is three orders of magnitude higher than that of previously reported µDMFCs.